Diffuse large B cell lymphoma within an anal fistula: a case report with an intriguing possible aetiology. Issue 8 (16th August 2021) - Kent, James; Joske, David; Parry, Jeremy
Abstract: Described is a case of diffuse large B cell lymphoma that presented within a typical fistula tract, possibly secondary to oxidative stress within the fistula tract itself and consequent malignant change rather than a fistula as a consequence of necrosis in a lymphoma. If so it would be unique in the world literature. A 42-year-old fitness instructor presented with a typical appearing left lateral anal fistula. Biopsy of the fistulous tract revealed B cell lymphoma, graded 1E. Although chemotherapy cured the lymphoma, surgical treatment by ligation of the inter-sphincteric fistula tract was required to heal the fistula. At 3-year follow-up, there has been no recurrence of the lymphoma or the fistula. Neoplasia arising secondary to oxidative stress within an anal fistula is a well-established phenomenon. Early diagnosis of rare conditions associated with anal fistula can only be accomplished by routine biopsy of every fistula tract.